A process model of collaboration among educational institutions, local government units, non-government and business organizations, and the local church - Ysulat, Cornelio V., Jr. (Animo Repository, 2008)
This is a qualitative study aimed at proposing a model of collaboration among different sectors in the province of Antique: diocesan schools, local government unit, non-government units, business sector, and the Catholic Church. Data were gathered from a theoretical sample of leaders and selected members in those sectors through focused group discussions and executive interviews, as well as from relevant documents. Qualitative data analysis revealed that the different sectors are aware of existing conditions in their community, particularly of aspects that can either hinder or facilitate the formation and success of multi-sector collaboration among them. The different sectors also have a vision or dream of their desired future which they think can be achieved through collaborative processes. These findings, translated into propositions, yielded the model proposed in the study.